Ecology of the interaction between Ixodes loricatus (Acari: Ixodidae) and Akodon azarae (Rodentia: Criceridae) - Colombo, Valeria Carolina (2015)
The present study explores associations of different factors (i.e. host parameters, presence of other ectoparasites and [mainly biotic] environmental factors) with burdens of Ixodes loricatus immature stages in one of its main hosts in Argentina, the rodent Akodon azarae. For 2 years, rodents were trapped and sampled monthly at 16 points located in four different sites in the Parana River Delta region. Data were analysed with generalized linear mixed models with a negative binomial response (counts of larvae or nymphs). The independent variables assessed were (a) environmental: trapping year, presence of cattle, type of vegetation, rodent abundance; (b) host parameters: body length, sex, body condition, blood cell counts, natural antibody titers and (c) co-infestation with other ectoparasites. Two-way interaction terms deemed a priori as relevant were also included in the analysis. Most of the associations investigated were found significant, but in general, the direction and magnitude of the associations were context-dependent. An exception was the presence of cattle, which was consistently negatively associated with both larvae and nymphs independently of all other variables considered and had the strongest effect on tick burdens. Mites, fleas and Amblyomma triste were also significantly associated (mostly positively) with larval and nymph burdens, and in many cases, they influenced associations with environmental or host factors. Our findings strongly support that raising cattle may have a substantial impact on the dynamics of I. loricatus and that interactions within the ectoparasite community may be an important—but generally ignored—driver of tick dynamics.